Komunikasi Organisasi di Kantor Kecamatan Cisaat Kabupaten Sukabumi - Moch Dendi Saputra (STISIP Widyapuri Mandiri Sukabumi, 2025)
Organizational communication is a complex process involving formal and informal interactions. This study aims to analyze the communication flow within the Cisaat District Office, including downward, upward, horizontal, and diagonal communication. The research adopts a qualitative descriptive approach with interviews and observations as primary data collection methods. The findings indicate that while horizontal and diagonal communication are effectively implemented, upward and downward communication still face challenges, impacting work motivation and organizational effectiveness. Improving communication strategies could enhance efficiency and employee engagement.